An X‐ray gas monitor for free‐electron lasers. (12th June 2019) - Sorokin, Andrey A.; Bican, Yilmaz; Bonfigt, Susanne; Brachmanski, Maciej; Braune, Markus; Jastrow, Ulf Fini; Gottwald, Alexander; Kaser, Hendrik; Richter, Mathias; Tiedtke, Kai
Abstract : Characterization of the absolute photon pulse energy and beam position of free‐electron lasers (FELs) is essential for many user experiments, as well as for machine operators. Described here is an X‐ray gas monitor which is a suitable tool for FEL photon diagnostics over a broad spectral range from vacuum ultraviolet to hard X‐rays. Abstract : A novel X‐ray gas monitor (XGM) has been developed which allows the measurement of absolute photon pulse energy and photon beam position at all existing and upcoming free‐electron lasers (FELs) over a broad spectral range covering vacuum ultraviolet (VUV), extreme ultraviolet (EUV) and soft and hard X‐rays. The XGM covers a wide dynamic range from spontaneous undulator radiation to FEL radiation and provides a temporal resolution of better than 200 ns. The XGM consists of two X‐ray gas‐monitor detectors (XGMDs) and two huge‐aperture open electron multipliers (HAMPs). The HAMP enhances the detection efficiency of the XGM for low‐intensity radiation down to 10 5 photons per pulse and for FEL radiation in the hard X‐ray spectral range, while the XGMD operates in higher‐intensity regimes. The relative standard uncertainty for measurements of the absolute photon pulse energy is well below 10%, and down to 1% for measurements of relative pulse‐to‐pulse intensity on pulses with more than 10 10 photons per pulse. The accuracy of beam‐position monitoring in the vertical and horizontal directions is of the order of 10 µm.